O cuidado de diabéticos insulinodependentes: pistas para ações na atenção básica em saúde - Moutinho, Daniela Gonçalves Godoy [UNIFESP] (2016)
The study aimed to describe and to analyze problem-based workshops conducted with insulin dependent diabetics from one primary health care unit, located in one vulnerable neighborhood. Methods: An intervention-research was conducted with 14 diabetics from this neighborhood, with mean age 62,5 years (median = 64 years). Participants were selected from the unit?s Hiperdia System, and from the unit?s internal register of insulin dependent diabetics. From 291 records, 126 were selected due to outdated registers. Of these, 14 participated in the study. The meetings were organized in workshops format. In the first meeting, participants answered na socioeconomic questionnaire and to the guiding question, in order to list generating topics.In the following meetings these topics were deepened considering scientific and popular knowledge. Several strategies were used, namely food degustation, videos, circle of conversation, among others. Results and discussion: According to the participants responses to the guiding question, the main difficulties in care were: restrictive diet, relationship with health care professionals, insulin therapy, and socioeconomic matters. These generating topics provided direction to the intervention workshops. The degustation strategie brought new flavors to the diabetics taste, enabling a better perspective regarding diet without added sugar. From the research process, clues to insulin dependent diabetics care in primary attention: 1. Diabetics surveillance and attendance; 2. Educational groups to the diabetic care; 3. Interdisciplinary care; 4. Intersectoral action care. The difficulties and clues found converge with previous studies regarding primary care and diabetes care, specially when considering vulnerable populations. Final considerations: The use of workshops in diabetes care can render an horizontalized education, and can potentiate the knowledge exchange between participants. It also allows the management of interventions in group contexts and from daily problems experienced by individuals, families, comunity and neighborhood. It is believed that knowledge exchange interventions can potentiate selfcare.